2003
DOI: 10.1016/j.bbamcr.2003.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Cycloserine and threo-dihydrosphingosine inhibit TNF-α-induced cytotoxicity: evidence for the importance of de novo ceramide synthesis in TNF-α signaling

Abstract: Measuring the cell death induced by tumor necrosis factor (TNF-alpha) in L929 cells, we discovered for the first time that L-cycloserine, an established inhibitor of serine palmitoyltransferase, as well as DL-threo-dihydrosphingosine (threo-DHS, threo-sphinganine) significantly protected against TNF-alpha-induced cytotoxicity. Under the same conditions sphingosine and DL-erythro-dihydrosphingosine (erythro-DHS) did not change TNF-alpha-induced cytotoxicity, thus underlining the specificity of threo-DHS. In ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 16 publications
1
24
0
Order By: Relevance
“…TNF-␣ has been shown to elevate cellular ceramide by both stimulating de novo ceramide synthesis (82,83) and increasing ceramide generation from sphingomyelin hydrolysis (84). In this study, we found an age-associated elevation in both TNF-␣ and ceramide and, thus, one might argue that the higher ceramide levels are due to elevated TNF-␣ production with aging.…”
Section: Discussionsupporting
confidence: 46%
“…TNF-␣ has been shown to elevate cellular ceramide by both stimulating de novo ceramide synthesis (82,83) and increasing ceramide generation from sphingomyelin hydrolysis (84). In this study, we found an age-associated elevation in both TNF-␣ and ceramide and, thus, one might argue that the higher ceramide levels are due to elevated TNF-␣ production with aging.…”
Section: Discussionsupporting
confidence: 46%
“…In TNF-α signaling, de novo synthesis via serine palmitoyltransferase action has been demonstrated [32].…”
Section: Discussionmentioning
confidence: 99%
“…These proteins in turn phosphorylate IRS and the insulin receptor, leading to inhibition of insulin signaling (Weickert & Pfeiffer 2006). Secondly, TNFa can activate de novo ceramide synthesis, likely via induction of sphingomyelinase that converts sphingomyelin to ceramides (Chatterjee 1993, Meyer & de Groot 2003. In turn, ceramides, concomitantly with DAG, activate different kinases interacting with IRS phosphorylation, finally inhibiting insulin signaling (Griffin et al 1999, Itani et al 2002, Summers 2006.…”
Section: Tumor Necrosis Factor Amentioning
confidence: 99%
“…Therefore, several controversies remain to be clarified regarding the pathological role of TNFa in NAFLD. Xu et al (2002) TNFa is present in white adipose tissue and its production is significantly increased in different rodent obesity models Arner (2003) TNFa level correlates with insulin resistance Hotamisligil (2003) Blocking TNFa with an antibody increases insulin sensitivity Uysal et al (1997) Mice lacking TNFa function are protected against obesity-induced insulin resistance Meyer & de Groot (2003) TNFa induces cytotoxicity through regulation of ceramide synthesis Tilg & Diehl (2000) Increased TNFa level in NAFLD patients Lesmana et al (2009) Correlation between TNFa and degree of liver fibrosis in NAFLD subjects Zhou et al (2010) High prevalence of certain TNFa polymorphisms in patients with NAFLD Lee et al (2008) Pharmacological inhibition of TNFa reduces aminotransferase levels in patients with NAFLD IL6 Bastard et al (2002) IL6 produced by white adipose tissue contributes to insulin resistance observed in obese humans El-Assal et al (2004) IL6 protects against ethanol-induced liver injury Wallenius et al (2002) IL6-deficient mice develop mature onset obesity and associated insulin resistance Wieckowska et al (2008) Hepatic IL6 expression correlates with the severity of NAFLD Yamaguchi et al (2010) Blocking IL6 prevents liver damage and enhances liver steatosis In summary, metabolic alterations leading to lipid accumulation promotes local TNFa production (e.g. liver) and kinase activation.…”
Section: Tumor Necrosis Factor Amentioning
confidence: 99%